Determination of higher order stress terms in cracked Brazilian disc specimen under mode I loading using digital image correlation technique. (November 2018) - Moazzami, Mostafa; Ayatollahi, Majid R.; Chamani, Hamid R.; Guagliano, Mario; Vergani, Laura
Highlights: Digital Image Correlation (DIC) method is used for determining crack tip parameters. Higher order terms of crack are obtained for Cracked Brazilian Disk (CBD) specimen. Different crack lengths are considered in the specimens tested by DIC method. The experimental results are validated by previous data available in literature. Good agreement exists between the DIC and finite element results. Abstract: The digital image correlation (DIC) technique is used to calculate the coefficients of higher order terms of the Williams' expansion in the centrally-cracked Brazilian disc specimens of different crack lengths under pure mode I loading. The specimens are subjected to diametral-compression loading and the displacement field is obtained for the cracked Brazilian disc by a correlation between the undeformed and deformed images captured before and after loading. The rigid body motion and rotation of each specimen are detected and eliminated from the displacement field by using a code developed based on the Williams' series solution. Then, by employing an over-deterministic system of equations, the coefficients of higher order terms of the Williams expansion are calculated. The same specimens are then simulated using finite element method. It is shown that there is good agreement between the DIC and the finite element results. Therefore, the DIC technique can be proposed as a reliable method to experimentally obtain the mode I stress intensity factor KI, the T-stress and the coefficients of higher order terms in the Williams' series expansion.